Morphofunctional analysis of the quadrate of Spinosauridae (Dinosauria - Hendrickx, Christophe (2016)
The Association des Geologues Amateurs de Belgique (AGAB), granted to C. H. for this research project at the Ulg. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.